2015
DOI: 10.3390/ijerph121114216
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Psychological Effects of a Walk in Urban Parks in Fall

Abstract: In recent times, attention has been focused on the role of urban green spaces in promoting human health and well-being. However, there is a lack of evidence-based research on the physiological effects of walking in urban green areas. This study aimed to clarify the physiological and psychological effects of walking in urban parks during fall. Twenty-three males (mean age 22.3 ± 1.2 years) were instructed to walk predetermined 15-min courses in an urban park and in a nearby city area (control). Heart rate and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
150
4
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 156 publications
(166 citation statements)
references
References 46 publications
11
150
4
1
Order By: Relevance
“…Similar results are obtained even after only about 15 to 20 minutes of walking in the forest [8][9][10][11][12]. This highlights the importance of green spaces in the city [14] and garden walking [15].…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Similar results are obtained even after only about 15 to 20 minutes of walking in the forest [8][9][10][11][12]. This highlights the importance of green spaces in the city [14] and garden walking [15].…”
Section: Discussionsupporting
confidence: 76%
“…These studies measured cortisol in saliva, sympathetic and parasympathetic functions, blood pressure, and heart rate variability as indices of stress. Some studies have included walking in addition to spending time in forests, but with walking times as short as 15 minutes [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that natural environments or nature-derived stimuli, such as forests [36][37][38][39][40][41][42], urban parks [43][44][45], flowers [46][47][48][49][50], and foliage plants [51,52], induce physiological relaxation in humans. Wood is a familiar natural material which we have many opportunities to touch on a daily basis, and it is used for many household objects, such as interior materials of buildings and houses, furniture (desks and shelves), and stationery.…”
Section: Discussionmentioning
confidence: 99%
“…This day fell in the spring period with increasing temperature and elongating daylight when phenology started at the initial blooming but air temperature had not been so high to make people feel uncomfortable. Although university students can also perceive mental restoration in an urban forest in fall (Song et al 2015b) and winter (Song et al 2013), more studies demonstrated the perceived response to forest bathing in spring (Ohtsuka et al 1998, Sonntag-Öström et al 2015b). Ohtsuka et al (1998) considered that the numerous negative ions in the forest in spring gave people a feeling of refreshment and exposure to negative ions can enhance parasympathetic nervous activity and decrease blood glucose levels.…”
Section: Discussion the Employment Of Spring Time In Maymentioning
confidence: 99%
“…Given the fact that the tree species in our study were broad-leafed, we consider that there may exist some tree-species significance in the effect of forest bathing on perceived anxiety alleviation. Although few studies have focused on this issue, studies about forest bathing suggested that the significant effect on mental restoration also accompanied by hard-wood species of oak (Park et al 2007, Lee et al 2009, Han et al 2016) and maple (Lee et al 2014, Song et al 2015b, Han et al 2016). In addition, more studies suggested that the forest bathing effect on anxiety alleviation was accompanied by coniferous tree species, such as Japanese cypress (Chamaecyparis obtusa) (Lee et al 2014, Song et al 2015a, Zhang et al 2015, Song et al 2016) and pine (Pinus spp.)…”
Section: Discussion the Employment Of Spring Time In Maymentioning
confidence: 99%